Avaliação dos critérios técnicos de qualidade das informações sobre dengue disponíveis na internet: um estudo infodemiologico - Silva, Enrieth Karoline dos Santos (Universidade Federal de São Carlos, 2024)
With the ease of access to information available on the Internet, the quality of such information can be questionable. Information is not always evidence-based, particularly in crisis situations like pandemics. Crisis situations can generate an overabundance of information, referred to as infodemia, where some information is accurate and true while others are not, making it difficult for people to find reliable sources and guidance when needed (Eysenbach, 2002). In this context, the present study aims to: Evaluate the quality of information available about Dengue on Brazilian URLs. Methodology: This is an exploratory, descriptive, cross-sectional infodemiological study with a quantitative approach that involves analyzing web pages based on CTQs (Critical Quality Indicators), conducted through dichotomous searches. Data were collected in February and analyzed in March and April 2024. Results: The first 200 URLs were selected and entered into an Excel spreadsheet. After excluding 8 URLs for various criteria, 192 pages were analyzed. Of these, 64 (33.33%) had identified authors, with only 18 (9.37%) being from relevant institutions. Only 21 (10.93%) provided complete author credentials, and many were not specialists in the field. Regarding the institutions responsible for the sites, 175 (91.14%) were identified, but none declared conflicts of interest. Most pages (134, or 69.79%) indicated the publication date, and 18 (9.37%) showed the update date. Only 48 (25%) included references and 21 (10.93%) had direct links to sources. Only one page indicated the level of clinical evidence, and 13 (6.77%) mentioned editorial review. All pages denied explicit sponsorship, raising concerns about potential undisclosed sponsors. Additionally, 119 (61.97%) pages had search tools and 110 (57.29%) provided contact information. 27 (14.06%) pages displayed content-related advertisements, and 33 (17.18%) promoted the sale of products, justifying the presence of ads as support for producing reliable content. Conclusion: The results indicate that although a significant portion of the websites reveals the responsible institution and publication date, there is a lack of transparency regarding authorship, credentials, and potential conflicts of interest. The low incidence of information about content updates, detailed references, and peer review points to the need to improve the quality and reliability of online information about dengue. The presence of advertisements and lack of transparency about sponsorships are also aspects that need to be addressed to ensure the integrity and impartiality of the content disseminated.
Evaluation of the technical criteria of quality of dengue information available on the internet: a infodemiological study
Keywords: Infodemiology; Infodemia; Dengue; Health Information; Internet; informação em saúde; CIENCIAS DA SAUDE::ENFERMAGEM